Dádivas de além-túmulo: circulação e hierarquia no espiritismo Kardecista - Barbosa, Allan Wine Santos (2018)
This research aims to ethnographically study the circuits of exchange that are established between incarnated and disincarnated agents in the activities of a spiritist center in the city of São Carlos (state of São Paulo). Through the description of what is done on a daily basis within a spiritist institution, the analysis seeks to apprehend the circuits of gifts and hierarchical processes involved in lectures, psychic sessions, prayers, passes, study groups and charitable practices, focusing on the effects of relationships thus established and its centrality in the construction of the spiritist notion of person. Spiritist practitioners establish their religious experiences around the movement of energies, words, spirits, knowledge, healing, feelings, messages, objects, etc. Such sets of spiritual and material goods constantly traverse the planes of existence (physical and spiritual) and evolutionary layers that make up the kardecist view of the cosmos. This image of the universe is organized in terms of hierarchical levels, a principle that also guides relationships between incarnated and disincarnated actors on Earth. The discussion of these aspects, alongside with a reflection on reciprocity and debt, aims to offer an understanding of spiritism as a system – morally and cosmologically – for circulation, enabling a relational and dynamic perspective of the daily religious experiences in the spiritist center.